The Canary record of the evolution of the North Atlantic Pliocene: New Ar-40/Ar-39 ages and some notable palaeontological evidence - Meco, J.; Koppers, Anthony A. P.; Miggins, Daniel P.; Lomoschitz, Alejandro; Betancort-Lozano, Juan Francisco (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Two new 40Ar/39Ar ages (*) and previously published K/Ar ages of basaltic pillow lava flows are coeval with closely-related fossiliferous marine layers, allowing us to establish the beginning (5.8; 5.0; 4.8Ma at Ajuí, Fuerteventura Island and 4.8±0.03Ma (2?)* at Tamaraceite) and a middle stage (4.20±0.18Ma (2?)* at La Esfinge in Gran Canaria Island) of Early Pliocene marine deposits in the Canary Islands. Here the presence of tropicopolitan fossils (Megaselachus megalodon, Janthina typica) suggests the influence of a possible Central American Circumtropical Current during the Pliocene and in the North Atlantic basin. 69 53 1,476 2,525 Q1 Q1 SCIE